Carbon Trading Literacy for Rural Communities - Tarigan, Vita Cita Emia; Siregar, Mahmul; Ekaputra, Mohammad; Rauf, Abdul; Idris, Siti Hafsyah (Universitas Sumatera Utara, 2024)
This research aims to explore the importance of carbon trading literacy in rural communities within the context of increasing awareness of climate change while enhancing village income. Understanding the concept of carbon trading becomes increasingly crucial. North Sumatra, with its diverse natural resources and economic sectors that have the potential to contribute to carbon emissions, has an urgent need to enhance carbon trading literacy among its populace. The research method used is literature review and interviews to gather data using a qualitative approach. The results indicate that the level of carbon trading literacy is still low, with limited understanding of the concept, benefits, and implications of carbon trading. Factors such as lack of access to information, education, and environmental awareness are major obstacles in enhancing carbon trading literacy in the community. The findings of this research highlight the urgency to enhance mentoring and education efforts regarding carbon trading.